Analisis Kemampuan Manajerial Kepala Sekolah dalam Mengintervensi Branding Sekolah di Tk Aisyiyah Kecamatan Besuki - Jamilatul Munawaroh (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The increasing number of educational institutions has intensified competition among schools, requiring them to develop strong branding to attract public interest. School branding is closely related to the managerial ability of the principal in managing resources, designing programs, and building the institution’s image. This study aims to describe the managerial ability of the principal in intervening in school branding at TK Aisyiyah, Besuki District. This research employed a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation involving the principal, teachers, and the parents’ association as informants. Data analysis was conducted through the stages of data collection, data reduction, data display, and conclusion drawing, while data validity was ensured through technique and source triangulation. The results of the study indicate that the principal’s managerial ability in building school branding is carried out through four managerial functions: planning, organizing, actuating, and controlling. The planning stage involves formulating branding strategies through discussions with teachers, the foundation, and the parents’ association. The organizing stage is implemented through clear task distribution among teachers in various school activities. The implementation stage is realized through several flagship programs such as tahfidz, drum band, tapak suci, and outing class that become the school’s distinctive characteristics. Meanwhile, the controlling stage is conducted through monitoring and evaluating the implementation of school programs. These managerial abilities play an important role in strengthening school branding and increasing public trust in the educational institution.
Approved by Teddy
Keywords: Kemampuan Manajerial; Kepala Sekolah